Yearbook of the United Nations 1990 - United Nations (United Nations, 1990)
With its comprehensive coverage of political and security matters, human rights issues, economic and social questions, legal issues, and institutional, administrative and budgetary matters, the Yearbook of the United Nations is the most authoritative reference work available on the activities and concerns of the Organization. Fully indexed, the Yearbook includes the texts of all major General Assembly, Security Council and Economic and Social Council resolutions and decisions.